Unravelling Robin sequence. (15th November 2013) - van, Manouk J. S.; Joosten, Koen F. M.; Hoeve, Hans L. J.; Mathijssen, Irene M. J.; Koudstaal, Maarten J.; Wolvius, Eppo B.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The airway management of children with Robin sequence is controversial. This study provides an overview of a single‐center experience with the diagnosis and treatment of 59 children with Robin sequence. Study Design Retrospective cohort study. Methods We conducted a retrospective cohort study of 59 children (<1 year old) with Robin sequence managed between 2000 and 2010. Robin sequence was defined as the presence of mandibular hypoplasia and clinical signs of airway obstruction. Data were collected on demographic characteristics, the presence of a syndrome, the perinatal period, and the management of airway and nutritional problems. Results Eighteen children (31%) needed respiratory support because of severe respiratory distress, and a sleep study found obstructive apneas in another eight children who had been managed by prone positioning and/or monitoring. In the isolated group significantly fewer children needed respiratory support compared to the nonisolated group. After the age of 1 year, 10% of the Robin sequence cohort was still in need of treatment for obstructive symptoms. Almost half (47%) needed temporary nutritional support. Conclusions The prevalence of respiratory distress in children with Robin sequence is high. In most children, treatment with prone positioning was sufficient to relieve the airway obstruction. Successful treatment with prone positioning was significantly more often seen in children with an isolated Robin sequence. About one‐third of all Robin sequence children needed respiratory support in the neonatal and/or infant period. However, in childhood, only 10% of the total Robin sequence cohort was still dependent on respiratory support. Level of Evidence 4 Laryngoscope, 124:E203–E209, 2014